2017
DOI: 10.1111/anae.14123
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the prevention of airway complications – a narrative review

Abstract: SummaryDespite being infrequent, complications of airway management remain an important contributor to morbidity and mortality during anaesthesia and care of the critically ill. Developments in the last three decades have made anaesthesia safer, and this has been mirrored in the equipment and techniques available for airway management. Modern technology including novel oxygenation modalities, widespread availability of capnography, second-generation supraglottic airway devices and videolaryngoscopy provide the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
22

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 109 publications
2
88
0
22
Order By: Relevance
“…Although predominantly based on patients undergoing cardiothoracic surgery, this review correlates with previous work which showed that ROTEM-and TEG-based transfusion algorithms reduce transfusion requirements and outperform standard coagulation tests in the setting of peripartum and trauma haemorrhage [2,3].…”
Section: Advances In Thromboelastograph Technologysupporting
confidence: 54%
See 1 more Smart Citation
“…Although predominantly based on patients undergoing cardiothoracic surgery, this review correlates with previous work which showed that ROTEM-and TEG-based transfusion algorithms reduce transfusion requirements and outperform standard coagulation tests in the setting of peripartum and trauma haemorrhage [2,3].…”
Section: Advances In Thromboelastograph Technologysupporting
confidence: 54%
“…Awake fibreoptic intubation of a patient with an obstructed upper airway is among the more challenging of airway procedures [1]. A multidisciplinary approach to safe management is essential [2], with an experienced Ear, Nose and Throat (ENT) surgeon immediately available to perform emergency surgical tracheostomy should awake fibreoptic intubation performed by an experienced anaesthetist fail to secure the airway.…”
mentioning
confidence: 99%
“…Numerous studies have evaluated individual patient‐related risk factors as dichotomous stand‐alone tests for predicting difficult airway management, but with limited overall diagnostic value . Multivariate sum scores, or the combination of several risk factors, gather more information and potentially increase the diagnostic accuracy . Like stand‐alone tests, a multivariate sum score may be used as a dichotomous test with a single cut‐off value to discriminate between easy and difficult airway management.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials can be difficult to conduct in emergency settings due to the diverse caseload, obtaining consent, confounding factors, funding and human factors . It is now recognised that observational data and audit of quality improvement initiatives can lead to substantial improvement in patient care …”
Section: Insightsmentioning
confidence: 99%
“…12,13 It is now recognised that observational data and audit of quality improvement initiatives can lead to substantial improvement in patient care. 14 With careful planning, consensus can be achieved to allow standardised reporting formats. 15,16 Collaboration and merging of databases can investigate large numbers of patients across multiple different services and countries.…”
Section: Insightsmentioning
confidence: 99%